Non-Observance Maxims in Banyumasan Humor Speech - Wijiasih Eka Pertiwi (Journal Corner of Education, Linguistics, and Literature, 2023)
Humorous utterances can cause humor because listeners, readers and audiences find unexpected utterances, attitudes or things, language games and deviations in speech conveyed by a speaker or comedian due to a discrepancy between the concept and the actual situation and exaggerated and unreasonable expressions, so it can cause laughter. In a conversation, what the speaker means often goes beyond what is said. Other implied meanings can be inferred and predicted based on the context. Implicature can occur due to a violation of the principle of conversation. The violation of the cooperative principle has the aim of creating humor in the conversation. There is another basic theory of cooperative principle, namely the non-observance of the conversational maxims theory proposed by Grice (1975). It is one of the pragmatic studies in determining the implied meaning of utterances that contain humor. This study aims to analyze the non-observance maxims found in Banyumasan  humorous utterances on youtube. The data collection technique in this study was to use a purposive sampling technique, namely by looking for videos that match the research object. The methods used in this research were observation, documentation and transcription. The data analysis technique in this study used descriptive qualitative data analysis techniques and was carried out through three stages according to the data analysis model of Miles and Huberman (1984), namely data reduction, data presentation and drawing conclusions. The results of the study showed that in Banyumasan  humorous utterances there are several non-observance maxims, including flouting the maxims, violating the maxims and infringing the maxims. From these data, the most common is the flouting of quality maxims. This is because in humorous utterances there are non-observance of maxims that aim to create a funny impression.